Insights Into Management of Atrial Fibrillation in Asia Pacific Gained From Baseline Data from REgistry on Cardiac rhythm disORDers (RecordAF-Asia Pacific [AP]) Registry - Amerena, John; Chen, Shih-Ann; Sriratanasathavorn, Charn; Cho, Jeong-Gwan; Huang, Dejia; Omar, Razali; Tse, Hung Fat; King, Anthony (The American journal of cardiology, 2012)
The burden of atrial fibrillation (AF) and the lack of data on AF and its management in the Asia Pacific highlight the need for a comprehensive prospective study of AF management in this region. To address this need, the REgistry on Cardiac rhythm disORDers (RecordAF-Asia Pacific [AP]) has been initiated to assess the management of AF in 8 countries across the Asia Pacific. RecordAF-AP is a prospective, observational survey of the management of recently diagnosed AF with 1 year of follow-up. Eligible patients with AF, treated or not, were included in the registry; with data recorded prospectively during the follow-up visits at 6 and 12 months. A total of 2,721 patients with AF were recruited, of whom 2,629 were eligible for evaluation (intent-to-treat population). At study inclusion, rhythm- and rate-control strategies were applied to 37% (n = 959) and 62% (n = 1,610) of the patients, respectively. At baseline, the rhythm-control patients were mainly prescribed class III agents (49%), class Ic agents (39%), or β blockers (except for sotalol; 35%). The rate-control patients were mainly prescribed β blockers (except for sotalol; 57%) or cardiac glycosides (32%). Patients receiving rate-control strategies were more likely to have a history of heart failure or valvular heart disease and persistent AF. In contrast, those receiving rhythm-control strategies were more likely to have recently diagnosed or paroxysmal AF. In conclusion, RecordAF-AP will provide much needed insight into the real-life management of patients with AF in the Asia Pacific region.